Meningkatkan Sikap Ilmiah Siswa Abad 21 Melalui Kegiatan Eksperimen pada Materi Fotosintesis - Mala Sastia Novita Sari; Isslandy Ayu Hermalia; Tri Bagoes Pranoto Sanjoyo; Izza Arumi Rachmawati; Nita Kusuma Renata; Ani Anjarwati (Departement of Mathematics Education, 2023)
Science cannot be separated from global developments which are commonly referred to as the 21st century. Science and technology are developing. students in the 21st century are students from the Z or millennial generation where this generation is familiar with the development of science and technology. The aim of the researchers is to improve the scientific attitude of 21st century students through experimental activities on scientific problems, the problem that is found is in learning the process of photosynthesis. Researchers used qualitative research with a class action research approach or (Classroom Action Research). The results obtained in the first cycle and the second cycle get an increase, which means that using experimental research can increase students' scientific understanding.